Learning More from Political Communication Experiments: Pretreatment and Its Effects - Druckman, James N.; Leeper, Thomas J. (American journal of political science, 2012)
Research on political communication effects has enjoyed great progress over the past 25 years. A key ingredient underlying these advances is the increased usage of experiments that demonstrate how communications influence opinions and behaviors. Virtually all of these studies pay scant attention to events that occur prior to the experiment—that is, in "pretreatment events." In this article, we explore how and when the pretreatment environment affects experimental outcomes. We present two studies—one where we control the pretreatment environment and one where it naturally occurred—to show how pretreatment effects can influence experimental outcomes. We argue that, under certain conditions, attending to pretreatment dynamics leads to novel insights, including a more accurate portrait of the pliability of the mass public and the identification of potentially two groups of citizens—what we call malleability reactive and dogmatic.